Can the nutritional geometric framework unveil how macronutrients in pollen shape solitary bee foraging and survival? - Jaya Sravanthi Mokkapati; Natalie Boyle; Pierre Ouvrard; Adrien Sicard; Christina M. Grozinger (Royal Society Open Science)
The nutritional geometric framework (NGF) hypothesizes that animals forage to achieve specific macronutrient ratios. Pollen, the primary source of protein and lipids for bees, varies in nutritional content across plant species. Studies suggest some bumblebee species forage based on species-specific macronutrient preferences, regardless of floral traits. Here, we examine whether females of the solitary bee species, Megachile rotundata, also follow the NGF when foraging. In a semi-field experiment using Capsella recombinant inbred plant lines with varying pollen protein-to-lipid (P : L) ratios, M. rotundata visits were positively associated with pollen protein content. In a laboratory-based study using synthetic diets with varying P : L ratios, female M. rotundata consumed the most and survived longest on diets with intermediate P : L ratios (5 : 1 and 10 : 1). Paired-choice experiments further revealed that bees regulated nutrient intake, converging on an average intake of 6.6 : 1 ± 1.6 P : L. These results suggest that M. rotundata exhibits a clear macronutrient preference and regulation behaviour, optimizing nutrient intake consistent with a functional nutritional target. Understanding how macronutrients influence foraging preferences and health outcomes in diverse bee species is crucial for understanding how plant-pollinator networks evolved and creating habitats beneficial for diverse pollinators.